Development and early‐stage evaluation of a patient portal to enhance familial communication about hereditary cancer susceptibility testing: A patient‐driven approach. (20th January 2023) - Pollard, Samantha; Weymann, Deirdre; Loewen, Rosalie; Nuk, Jennifer; Sun, Sophie; Schrader, Kasmintan A.; Hessels, Chiquita; Regier, Dean A.
Abstract: Introduction: Genetic testing for hereditary cancer syndromes (HCSs) can improve health outcomes through cancer risk mitigation strategies. Effective communication between tested individuals and their family members is key to reducing the hereditary cancer burden. Our objective was to develop a patient portal to improve familial communication for patients undergoing HCS genetic testing, followed by an early‐phase evaluation. Methods: The portal was developed following the completion of 25 semistructured interviews with individuals having undergone HCS susceptibility testing at BC Cancer. Following initial development, we recruited patients and healthcare providers to provide critical feedback informing portal refinement. Quantitative feedback was summarized using descriptive statistics, and qualitative feedback was synthesized by two reviewers who engaged in iterative discussion within the research team to prioritize recommendations for integration. Results: The patient portal includes four key components consisting of (a) targeted educational information about hereditary cancer and HBOC syndrome associated risks and testing process overview, (b) a general frequently asked questions 'FAQ' page informed by the qualitative interviews, patient partner feedback,  and consultation with the HCP, (c) guidance to support familial communication including a video developed with a patient partner describing their lived experience navigating the communication process and (d) a series of lay summaries of genetic test findings to support information transfer among family members. Thirteen healthcare providers and seven patients participated in user testing. Domains within which participant recommendations were provided included presentation, educational content and process clarification. Conclusions: This investigation demonstrates the value of continual integration of patient and provider preferences through the development of tools endeavouring to assist with complex genomics‐informed decision‐making. Our work aims to broaden the population‐wide impact of HCS testing programs by improving communication processes between probands and their potentially affected family members. Patient or Public Contribution: This work involved a patient partner who was actively engaged in all aspects of the research investigation including protocol development, review and editing of all study documentation (including that of the previously published qualitative investigation), interpretation of results, as well as reviewing and editing the manuscript. Patient partners and healthcare professionals were recruited as research participants to provide critical feedback on the patient portal.